PENGARUH PROMOSI TERHADAP PENINGKATAN PENJUALAN PADA PT. COLUMBIA KOTAMOBAGU - DESIASTUTY PAPUTUNGAN; Johny R. E. Tampi; Olivia Walangitan (JURNAL ADMINISTRASI BISNIS, 2017)
To maintain the viability of the company, companies are often faced with the problem,such as the difficulty in increasing the volume of sales of the existence of competition fromsimilar companies increased the complexity of consumer behavior against a product,changing consumer tastes, as well as the uncertain economic conditions. Promotion is anactivity that can be done by the company with the aim to inform, persuade, and influenceconsumers to select or purchase products offered by the company. Promotions at ColumbiaKotamobagu PT. is seen from the 6 indicators i.e. advertising, personal selling, salespromotion, public relations, direct marketing tools, measurement scales use the ratin scale.This research is quantitative research using a simple correlation analysis and regressionanalysis. Data collection techniques in the study was collected in the form of primary dataand secondary data, and tools that on the collection of data through a questionnaire filledout by 300 respondents and analyzed using a simple correlation analysis and analysissimple regression. Based on the results of the analysis of simple correlation and simpleregression analysis showed that the independent variable is. promotion of the dependentvariables simultaneously affecting the increase in sales which means promotion toincreased influence sales are still in the low category. It is recommended also to companyPT. Columbia Kotamobagu so need to pay attention to the marketing mix policy especiallythe issue price is set so that the company can be reached by the consumer, so that it canincrease the level of sales.Keywords: promotion, increased sales